2012
DOI: 10.1017/s1461145712000314
|View full text |Cite
|
Sign up to set email alerts
|

Striatal glutamate and the conversion to psychosis: a prospective 1H-MRS imaging study

Abstract: Increased glutamate levels in the associative-striatum have been described in subjects at ultra-high risk for psychosis (UHR); nevertheless, it is unclear whether this abnormality predicts the conversion to psychosis. Nineteen subjects at UHR and 26 controls were studied using proton magnetic resonance spectroscopy. Subjects at UHR were clinically followed for 2 yr. Seven UHR subjects (37%) transitioned to a psychotic disorder and the remaining 12 did not exhibit psychotic symptoms at the most recent follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 21 publications
5
40
1
Order By: Relevance
“…The effect of antipsychotic medication on MRS measures remains unknown. Some off medication studies reported higher levels of glutamatergic metabolites (de la Fuente-Sandoval et al, 2011, 2013a, 2013bKegeles et al, 2012;Kraguljac et al, 2013), whereas others reported reduced or no difference (Goto et al, 2012;Wood et al, 2008). However, higher levels of glutamatergic metabolites do not appear to be specific to the off medication state since several studies reported higher glutamatergic metabolites in medicated patients (Aoyama et al, 2011;Bustillo et al, 2014;Chang et al, 2007;Theberge et al, 2003) and in treatment resistant patients taking medication (Demjaha et al, 2014;Egerton et al, 2012;Mouchlianitis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of antipsychotic medication on MRS measures remains unknown. Some off medication studies reported higher levels of glutamatergic metabolites (de la Fuente-Sandoval et al, 2011, 2013a, 2013bKegeles et al, 2012;Kraguljac et al, 2013), whereas others reported reduced or no difference (Goto et al, 2012;Wood et al, 2008). However, higher levels of glutamatergic metabolites do not appear to be specific to the off medication state since several studies reported higher glutamatergic metabolites in medicated patients (Aoyama et al, 2011;Bustillo et al, 2014;Chang et al, 2007;Theberge et al, 2003) and in treatment resistant patients taking medication (Demjaha et al, 2014;Egerton et al, 2012;Mouchlianitis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that our FEP group did not show such association raises the need for future studies to explore the moment along the illness course at which both measures become linked, as this could be informative in terms of both neurocognitive and psychosocial functioning decrease. Additionally, future crosssectional and longitudinal studies in larger samples are needed to address the heterogeneity of functional outcomes in the UHR population (Addington et al, 2011), prediction of conversion to full-blown psychosis (Cannon et al, 2008;Ruhrmann et al, 2010;de la Fuente-Sandoval et al, 2013), and the effect of psychotropic medication on this population.…”
Section: Discussionmentioning
confidence: 99%
“…Independent work has reported that both UHR and first episode subjects have higher levels of glutamate in the caudate nucleus than controls [80], and that UHR subjects that subsequently developed psychosis had higher striatal glutamate levels than UHR subjects who did not become psychotic [98]. A study that examined a medial prefrontal region failed to find altered glutamate or glutamine in UHR or first episode subjects, but did find reductions in chronic patients [99].…”
Section: Studies In Subjects At Uhr For Psychosismentioning
confidence: 99%